Zoonotic Potential of Rotavirus from Swine and Bovine in South of Taiwan - Murni, Dewi; Trisunuwati, Pratiwi; Liao, Ming Hui (Graduate School, Universitas Brawijaya, 2016)
Rotavirus was recognized as the virus that responsible for causing acute gastroenteritis, especially young livestock. Taiwan Center for Disease Control (CDC) confirms the majority cases of acute gastroenteritis in Taiwan on February 2015 were caused by rotavirus. In this study, we report the incidence and zoonotic impact of rotavirus strain from Taiwan. This study examined 90 (swine) and 60 (bovine) fecal samples collected from south of Taiwan in March 2015. Detection of rotavirus using VP6 gene by RT-PCR technique with amplicons 379 bp. Zoonotic potential analysis based on nucleotide sequence and phylogenetic analysis. RT-PCR utilizing the primers specific for VP6 gene detected rotavirus with positive reactions 3/30 (10%) in piglets and 1/20 (5%) in the calf. Based on the nucleotide sequences and phylogenetic analysis indicated that 1 of 3 wild strains from swine rotavirus had 85.0% - 91.1% and 1 wild strain from bovine had 78.7% - 85.9% identity relations with human strains. These findings indicated that the wild strains of swine and bovine rotavirus may broadly spread and contribute to zoonotic transmission. Keywords: Bovine, Rotavirus, RT-PCR, Swine, Zoonotic.